2021
DOI: 10.1101/2021.03.22.434418
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Drosophilaprimary microRNA-8 encodes a microRNA encoded peptide acting in parallel ofmiR-8

Abstract: Background: In the last decades, genome-wide studies of many species have revealed the existence of a myriad of RNAs differing in size, coding potential and function. Among these are the long non-coding RNAs (lncRNAs), some of them producing functional small peptides via the translation of short ORFs (sORFs). It now appears that any kind of RNA presumably has a potential to encode small peptides. Accordingly, our team recently discovered that plant primary transcripts of microRNAs (pri-miRNAs) produce small re… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…Until now, miPEPs have been shown to be encoded by the first open reading frame (miORF) after the transcription start site (TSS) located in the 5 0 region of the pri-miRNA and they enhance pri-miRNA transcription from which they originate (Lauressergues et al, 2015;Sharma et al, 2020;Chen et al, 2020). Initially characterized in Arabidopsis thaliana, Medicago truncatula, and Glycine max (Lauressergues et al, 2015;Couzigou et al, 2016Couzigou et al, , 2017, recent studies revealed the presence of miPEPs in other plant species (Chen et al, 2020;Zhang et al, 2020;Ormancey et al, 2021) and even in animals (Kang et al, 2020;Niu et al, 2020;Prel et al, 2021;Montigny et al, 2021;Immarigeon et al, 2021). This suggests that the number of miPEPs is probably far to be fully determined, and that miPEPs might be a common feature in both plant and animal kingdoms.…”
Section: Introductionmentioning
confidence: 99%
“…Until now, miPEPs have been shown to be encoded by the first open reading frame (miORF) after the transcription start site (TSS) located in the 5 0 region of the pri-miRNA and they enhance pri-miRNA transcription from which they originate (Lauressergues et al, 2015;Sharma et al, 2020;Chen et al, 2020). Initially characterized in Arabidopsis thaliana, Medicago truncatula, and Glycine max (Lauressergues et al, 2015;Couzigou et al, 2016Couzigou et al, , 2017, recent studies revealed the presence of miPEPs in other plant species (Chen et al, 2020;Zhang et al, 2020;Ormancey et al, 2021) and even in animals (Kang et al, 2020;Niu et al, 2020;Prel et al, 2021;Montigny et al, 2021;Immarigeon et al, 2021). This suggests that the number of miPEPs is probably far to be fully determined, and that miPEPs might be a common feature in both plant and animal kingdoms.…”
Section: Introductionmentioning
confidence: 99%